Saccharide Characteristics and Their Potential Health Effects in Perspective - Brouns, Fred (Frontiers in Nutrition, 2020)
To understand the effects of saccharides on our metabolism and health, we need to have a clear understanding of what they are and how they differ one from another, in a way that some types are being labeled ‘less healthy’ and others ‘better for health’. There are various ways to look at this. One approach is to classify saccharides according to their degree of polymerization (DP). Such a classification is useful when qualitative or quantitative analysis and calculation of intakes are required or for food labeling definition such as ‘added sugars are those having a DP of 1-2’. However, this does not account for the fact that saccharides having a similar DP can have differences in the chemical bonds between the individual monomers, which will influence the rate of digestion, absorption, hormonal responses and metabolic fate. In other words, DP only tells us a ‘part of the story’. Therefore, another approach used broadly in the biomedical and nutritional sciences is to classify carbohydrates (CHOs) according to their physiological responses. This will address the rate and degree of digestibility and absorption, the glycemic response, the conversion to other metabolites, the degree of oxidation or storage, etc. However, also this approach will not give a complete answer because the characteristics of the matrix/meal in which these CHOs are present will also influence the responses of our body. One can also rank CHOs by comparing their functional/technological properties such as for example relative sweetness, viscosity and solubility. Understanding CHO characteristics and related physiological responses will help understand health and disease implications. Therefore, in this overview a brief outline of different carbohydrate classifications is presented. This will be placed in the context of potential overall effects after consumption. Should we eat less of certain sugars? It depends! Partly because looking at one particular CHO characteristic will almost always lead to a different conclusion (fructose is toxic!) than when evaluating from a "total perspective", fructose is only toxic at excessive exposure levels that do not mimic human consumption. Examples are given to help understand this matter in favor of justified dietary/food recommendations.